The foraging behavior of nonbreeding Adélie penguins in the western Antarctic Peninsula during the breeding season. Issue 5 (19th May 2022) - Oosthuizen, W. Chris; Pistorius, Pierre A.; Korczak‐Abshire, Malgorzata; Hinke, Jefferson T.; Santos, Mercedes; Lowther, Andrew D.
Abstract: Information on marine predator at‐sea distributions is key to understanding ecosystem and community dynamics and an important component of spatial management frameworks that aim to identify regions important for conservation. Tracking data from seabirds are widely used to define priority areas for conservation, but such data are often restricted to the breeding population. This also applies to penguins in Antarctica, where identification of important habitat for nonbreeders has received limited attention. Nonbreeding penguins are expected to have larger foraging distributions than breeding conspecifics, which may alter their interactions with physical environmental factors, conspecifics, other marine predators, and threats. We studied the movement behavior of nonbreeding Adélie penguins tracked during the 2016/2017 breeding season at King George Island in the South Shetland Islands, Antarctica. We quantify how nonbreeding penguins' horizontal moment behavior varies in relation to environmental conditions and assess the extent of spatial overlap in the foraging ranges of nonbreeders and breeders, which were tracked over several years. Nonbreeders increased their prey search and area‐restricted foraging behavior as sea surface temperature and bottom depths decreased, and in response to increasing sea ice concentration. Nonbreeders tended to transit (high directional movement) over the relatively deep Central Basin of the Bransfield Strait. The majority of foraging behavior occurred within the colder, Weddell Sea–sourced water of the Antarctic Coastal Current (incubation) and in the Weddell Sea (crèche). The utilization distributions of breeders and nonbreeders overlapped in the central Bransfield Strait. Spatial segregation was greater during the crèche stage of breeding compared to incubation and brood, because chick provisioning still constrained the foraging range of breeders to a scale of a few tens of kilometers, while nonbreeders commenced with premolt foraging trips into the Weddell Sea. Our results show that breeding and nonbreeding penguins may not be impacted similarly by local environmental variability, given that their spatial and temporal scales of foraging differ during some part of the austral summer. Our study highlights the need to account for different life history stages when characterizing foraging behavior of marine predator populations. This is particularly important for "sentinel" species monitored as part of marine conservation and ecosystem‐based management programs.